Exploring Destination Brand Identity Of Lenggong Valley World Heritage Site From The Perspective Of Local Community - Musa, Norfardilawati (2022)
Strong and sustainable destination branding is critical for destinations to remain competitive in the current tourism industry. However, the existence of multiple stakeholders with different interests poses an intricate challenge. In addition to the challenge of identifying the multiple ‘owners’ of the destination, getting their consensus on the identity of the destination also proved to be difficult. Local community, as one of the destination’s key stakeholders and as the host of the destination, plays critical roles in stewarding tourism development and in providing rewarding experience to tourists. Therefore, their conceptualisation of the destination brand identity dimensions is critical in shaping tourism development in ways that will exude the values of the community and their heritage. This study proposes a framework to elucidate the Lenggong Valley World Heritage Site (LVWHS) dimensions of brand identity from the perspective of the local community. Adopting the qualitative method, the data collection was conducted in two phases – (i) in-depth interviews in exploring the identity dimension of destination from the micro perspective; and (ii) focus group discussion (FGD) in explaining the macro perspective, particularly in how the residents as members of a community arrive at a consensus on the brand identity of a destination. The participants of this research were purposively selected, consisting of the headmen and representatives of female residents to represent the local community’s perspectives